A congenital fibular notch synostosis of the left distal leg: a case report - Olubunmi Balogun; Oladayo oyedun; Olaniran Morakinyo; Olusegun Ajeleti; Olaleye Olabiyi; Gideon Ojo; Abayomi Olubintan (Journal of Research in Applied and Basic Medical Sciences)
Background & Aims: Tibiofibular synostosis is an infrequent, limb malformation that is non-syndromic and illustrated by the union of the proximal or distal tibia and union of the proximal or distal tibial and fibular metaphysis and/ or diaphysis. Congenital tibiofibular synostosis is a very rare anomaly and if there are no related syndromes or distortions, the cause may be unknown or acquired. The case presented here shows a fusion of the tibia and fibula at the fibular notch which is not secondary to a fracture, hematoma, or any procedure done to fix the distal tibiofibular joint, as shown by the x-ray radiograph. Among other factors, calcification of bleeding into the surrounding tissue may result in the fusion of the tibia and fibula. Case Presentation: After macerating the bone of a 56-year-old Nigerian male cadaver in the Anatomy Program, Bowen University, Nigeria, a dried adult left tibia and fibula with ossification at the distal end of both bones were observed. Anteriorly, a nutrient foramen was present where the anterior tibial vessels pass, while a number of grooves were observed posteriorly at the fused end. Thorough observation showed fusion of the distal tibiofibular syndesmosis joint with the absence of callus formation and /or a fracture. A bone specimen of distal tibiofibular synostosis and its medical importance are hereby highlighted. Conclusion: Cases of congenital distal tibiofibular synostosis are rare. When present in a living person, this should be suggestive to the physician who may be treating a patient who complains of ankle pain of unknown etiology. This is known to be a common reason for pain in the anterior leg compartment, usually associated with sports activities which may present with ankle pain as a result of abnormal ankle function.